Designed leucine‐rich repeat proteins bind two muramyl dipeptide ligands. (15th February 2021) - Kim, Christina S.; Brown, Anne M.; Grove, Tijana Z.; Etzkorn, Felicia A.
Abstract: Designed protein receptors hold diagnostic and therapeutic promise. We now report the design of five consensus leucine‐rich repeat proteins (CLRR4–8) based on the LRR domain of nucleotide‐binding oligomerization domain (NOD)‐like receptors involved in the innate immune system. The CLRRs bind muramyl dipeptide (MDP), a bacterial cell wall component, with micromolar affinity. The overall K d app values ranged from 1.0 to 57 μM as measured by fluorescence quenching experiments. Biphasic fluorescence quenching curves were observed in all CLRRs, with higher affinity K d1 values ranging from 0.04 to 4.5 μM, and lower affinity K d2 values ranging from 3.1 to 227 μM. These biphasic binding curves, along with the docking studies of MDP binding to CLRR4, suggest that at least two MDPs bind to each protein. Previously, only single MDP binding was reported. This high‐capacity binding of MDP promises small, soluble, stable CLRR scaffolds as candidates for the future design of pathogen biosensors.